Estimation of Total Digestible Nutrient Concentration for Short-Panicle Cultivars of Forage Rice (Oryza sativa L.) Silage - Satoru Fukagawa; Kyohei Ninomiya; Yasuyuki Ishii (Agronomy)
A linear regression model for predicting total digestible nutrient (TDN) concentration in forage rice (Oryza sativa L.) silage was previously developed with traditional cultivars (>30% dry matter, DM as panicle), and we here extend the linear regression model to two short-panicle cultivars, ‘Tachisuzuka’ and ‘Tachiayaka’ (<20% DM as panicle). Silage fermentation quality was superior for the short-panicle cultivars compared to the traditional ones, partly due to higher mono- and oligosaccharide concentrations in leaves and stems. Silage TDN concentration was previously estimated for traditional cultivars by in vitro dry matter digestibility (IVDMD) and crude ash (CA) concentration (estimated TDN = 0.329 × IVDMD − 0.688 × CA + 44.5, r2 = 0.815, p < 0.001). In vivo TDN concentration in silages of short-panicle cultivars, ranging from 49.5 to 58.3%, was nearly identical to the TDN concentration estimated by the equation with an error rate <5%, demonstrating that the new equation model can be satisfactorily applied to silages of short-panicle rice cultivars.